2014
DOI: 10.1155/2014/308058
|View full text |Cite
|
Sign up to set email alerts
|

Study on an Axial Flow Hydraulic Turbine with Collection Device

Abstract: We propose a new type of portable hydraulic turbine that uses the kinetic energy of flow in open channels. The turbine comprises a runner with an appended collection device that includes a diffuser section in an attempt to improve the output by catching and accelerating the flow. With such turbines, the performance of the collection device, and a composite body comprising the runner and collection device were studied using numerical analysis. Among four stand-alone collection devices, the inlet velocity ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…Total calculation grids were composed of 2.57-2.92 and 3.33-3.67 million elements for the single runner and composite body analyses, respectively. We confirmed that the dependency on the number of grids was relatively small by increasing the total number of calculation grids by 1.5 times [10]. The boundary conditions were flow velocity v ∞ = 1.5 m/s for the inlet boundary, arbitrary rotational speed for the runner, and a static pressure (gauge pressure) of 0 Pa for the outlet boundary.…”
Section: Methods and Conditions For The Numerical Analysissupporting
confidence: 61%
See 4 more Smart Citations
“…Total calculation grids were composed of 2.57-2.92 and 3.33-3.67 million elements for the single runner and composite body analyses, respectively. We confirmed that the dependency on the number of grids was relatively small by increasing the total number of calculation grids by 1.5 times [10]. The boundary conditions were flow velocity v ∞ = 1.5 m/s for the inlet boundary, arbitrary rotational speed for the runner, and a static pressure (gauge pressure) of 0 Pa for the outlet boundary.…”
Section: Methods and Conditions For The Numerical Analysissupporting
confidence: 61%
“…Using steady flow analysis, we previously studied the performance and flow field of the open-channel hydraulic turbine with respect to a single runner, a single collection device, and a composite body consisting of the runner and collection device. We also experimentally verified the effectiveness of this hydraulic turbine from analysis results [9,10]. Furthermore, we clarified the influence of the interference between the runners (with different number of blades) and an axially asymmetrical collection device of the hydraulic turbine [11].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations